Study of thunderstorm activity in Volyn Region and in Ukraine using the data of Blitzortung online resource - V. V. Fedoniuk; M. A. Fedoniuk; A. M. Pavlus (Український гідрометеорологічний журнал, 2021)
The article contains the results of statistical and graphical analysis of thunderstorm activity in Ukraine and within Volyn Region, in particular, following the study of the dynamic maps archive available at the online resource Blitzortung.org (lightnings and thunderstorms in real time). It describes the principles and results of activities of Blitzortung.org, a community of lightning direction sensors owners and users, and presents the developed algorithm of the methodology of reading dynamic maps available at this resource.